Implication of controlled embedment of graphite nanoplatelets assisted by mechanochemical treatment for electro-conductive polyketone composite - You, Jiwan; Kim, Jong-Hwal; Seo, Kwan-Ho; Huh, Wansoo; Park, Jong Hyuk; Lee, Sang-Soo (한국공업화학회, 2018)
The interfacial instability between fillers and polymer matrix has been of prime concern in preparing polymer composites of high performance, and large endeavors have been poured to solve the matter through functionalization of fillers. Considering the embedment of graphite nanoplatelet (GNP) to polymer for mechanically-robust composites of electro-conductivity, it would be essential to find out a method without employing oxidation-involved functionalization of GNP due to the structural degradation of GNP under harsh chemical oxidation reaction. Alternatively, based on the solvent-free mechanochemistry (MC)-involved GNP functionalization, we have proposed to complete an electro-conductive thermoplastic composite. It was notable that the MC-treated GNPs were extensively adhered on polyketone (PK) particles to form GNP-coated PK particles (G-PK) even without chemical functionalization, imparting successfully PK composite deploying controlled distribution of GNPs. As evidenced by the GNP distribution analyses through Raman mapping and X-ray tomography, the MC treated GNPs were distributed with a tendency to form a continuous network-like structure in PK matrix, while the untreated GNP exhibited random distribution of severely agglomerated GNPs, a typical morphology of the incompatible filler-containing polymer composites. The MC-assisted formation of G-PK and the following network-formed distribution of GNPs endowed the effective transport of electron, resulting in notable electrical conductivity of G-PK composites, especially even at small loading of GNP. The MC-assisted G-PK and the corresponding PK composite exhibiting network-like distribution of GNPs are believed to be efficient as a sustainable structural material requiring controlled electrical conductivity. (C) 2018 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.